Time to treatment initiation (TTI) and retrospective analysis of antiretroviral therapy (ART) outcomes among HIV-positive Methadone Maintenance Therapy clients In primary health care centres, Kuantan, Pahang. - Ramlan, Aida Roziana; Mohamed Nazar, Nor Ilyani; Tumian, Afidalina; Ab Rahman, Norny Syafinaz; Mohamad, Dzawani; Abdul Talib, Mat Sharil; Zakaria, Mohd Khairul Faizan; Izuddin, Muhammad Azzim; Zainal Abidin, Nadia Akmal; Tunku Syed Manso, Syarifah Syafiqah; W Hassan, W N Khairiyah (2019)
Introduction: Methadone Maintenance Therapy (MMT) program improves access to antiretroviral therapy (ART) among people who inject drugs (PWID) with HIV-positive status. However, the time to treatment initiation (TTI) and outcomes of ART intervention in this population has scarcely been analysed. Objectives: This study aimed to analyse the TTI and outcomes of ART among MMT clients in primary health care centres in Kuantan, Pahang. Materials and Methods: This is a retrospective evaluation of MMT clients’ records from the year 2006 to 2019. The TTI was calculated from the day of diagnosis to ART initiation. The trends of CD4 counts and viral loads were descriptively evaluated. Cox proportional hazard model was used to analyse the survival and treatment retention rate. Results: A total of 67 MMT clients from six primary health care centres were HIV-positive with 37 clients were started on ART. The mean TTI of ART was 27 months. The clients who were given ART had a median CD4 count of 119 cells/mm3 at baseline and increased to 219 cells/mm3 after six months of ART. Only two patients (5.4%) in the ART group had an unsuppressed viral load. The initiation of ART had reduced the risk of death by 72.8% (hazard ratio = 0.27, p=0.024), and they are 13.1 times more likely to retain in treatment (p<0.01). Conclusion: The TTI of ART was delayed in this population. MMT clients who were given ART have better CD4 and viral loads outcomes, helped reduced death risk and showed higher retention rates in the MMT program.